Renal Cell Carcinoma in Dialysis Patients with End Stage Renal Disease: Focus on Surgery and Pathology - Masuda, Hitoshi; Kihara, Kazunori; Fujii, Yasuhisa; Koga, Fumitaka; Saito, Kazutaka; Sakura, Mizuaki; Okada, Yohei; Kawakami, Satoru (IntechOpen, 2011)
None